Vocational Training Needs of Rural Youth in Agriculture for Self-employment in Udham Singh Nagar of Uttarakhand (Indian Journal of Extension Education, 2018)
Making rural youth employable is a big challenge to the menace of unemployment and underemployment. Government is putting efforts towards conducting skill based trainings as trained and productively engaged youth can bring miracles for the nation. The present study was carried out to find out the vocational training needs of rural youth in agriculture related areas. Qualitative and quantitative investigation was carried out in Udham Singh Nagar district of Uttarakhand using analytical research design. Youth (n=120) were selected from three villages representing agricultural progressiveness in decreasing order through disproportionate stratified random sampling. Pre-tested interview schedule was used for data collection. Maximum training need in major agricultural vocations was found to be in fruit and vegetable production (2.050) followed by cattle farming (2.008), Mushroom Production (1.975) Floriculture (Protected Cultivation) (1.933), Poultry (1.658), Vermi-culture (1.616), Fishery (1.541), Bee keeping (1.508), Rabbit farming (1.450) and Sericulture (1.425). Training needs in subareas of major vocations were also calculated. Village was the most favourable area in receiving training for about two months in Rabi season at the morning time. Scientists and demonstrators were preferred the most along with regular trainings and fortnight demonstrations. Among psychological characteristics, achievement motivation (r = 0.188, tcal=2.079) had a significant positive relationship with vocational training needs of rural youth whereas innovativeness, leadership ability, risk preference and occupational Aspiration had non-significant but positive relationships with vocational training needs of rural youth in agriculture related areas.